(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Background: Corticosteroids are an essential component of treatment for acute lymphoblastic leukemia (ALL). Prednisolone is the most commonly used steroid. There is increasing evidence that, even in equipotent dosage for glucocorticoid effect, dexamethasone has enhanced lymphoblast cytotoxicity and penetration of central nervous system compared with prednisolone. Objectives: To determine the effect of dexamethasone and prednisolone and to compare them in induction therapy of ALL in Children. Material & Methods: A total of 60 newly diagnosed cases of ALL confirmed by bone marrow study, children of either sex with age >1 year were included in this study. Variables studied were age, sex, presenting features, neutrophil count, blast cell count, platelet count, bone marrow status at diagnosis, on D15 & D29 of induction and side effects. Results: Mean age of the patients of group A was 6.28 years & that of group B was 7.2 years. Out of all patients of group A 19 (63.3%) were male and 11 (36.7%) were female. In group B 21 (70.0%) patients were male and rests 9 (30.3%) were female. No statistically significant difference was observed in both groups in terms of age, sex & presenting features. After induction significant difference was observed in liver & spleen size at day 7 and day 15. All patients of both groups had M3 marrow status at diagnosis. Overall, in group A 93.3% patients achieved M1 marrow status (fewer than 5% blasts) and 6.7% had M2 marrow status (5-25% blasts) at day 15 of induction. On the other side 66.7% patients of group B achieved M1 status and 33.3% M2 status at day 15. Statistically significant difference was observed between groups on day 15 in term of achieved marrow status (p<0.05). No statistically significant difference was observed between groups in term of infection in difference days of induction. On day 16 of induction maximum incidence of infection was observed in both groups. Conclusion: Dexamethasone may be an effective alternative option to prednisolone for the treatment of acute lymphoblastic leukemia in children. J. Paediatr. Surg. Bangladesh 6(1): 3-9, 2015 (Jan)